Indonesia's Policy Analysis of The Aukus Trilateral Defense Pact - Kennedy, Posma Sariguna Johnson; Sutrasna, Yudi; Haetami, H (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study aims to analyze the direction of the Indonesian government's policy in responding to the AUKUS (Australia-United Kingdom-United States) trilateral defense pact agreement and its relationship to the China- ASEAN conflict in the South China Sea based on the free and active policy adopted by Indonesia. The research method in this study uses a fully qualitative approach. The type of data used in this research is secondary, from various scientific articles and related news. ASEAN has become divided in addressing Australia's nuclearpowered submarine program together with the AUKUS Alliance. Countries give different reactions, some support, oppose, or observe. Responding to this, it becomes a challenge for Indonesia to continue to play an active role in escalating tensions between AUKUS and China, which can lead to military conflict and even nuclear war in the Indo-Pacific region. With free and active politics, Indonesia should be able to play the role. Position Indonesia is not included in the vortex of blocks or influences from superpower countries competing for influence/hegemony, especially in the Asia Pacific Region.